Development and Characterization of Sisal Fiber Reinforced Polypropylene Composite Materials - Gerezgiher, Alula Gebresas; Bsrat , Halefom Aregay; Simon, Andrea; Szabó, Tamás (International Journal of Engineering and Management Sciences, 2019)
In most of the developing countries, plastic polypropylene is not fully recycled and converted in-to use after it is once used. Sisal fiber is also widely available in different developing countries like Ethiopia. Adding this two materials and developing automotive interior part was taken as a primary motive for it reduces cost and is environmentally friendly. Thus, the main purpose of this research is to develop composite material from natural fibre (sisal fiber) reinforced with recycled plastic waste (polypropylene) for interior automobile accessories specifically for internal door trim panel application. This research examines effect of fiber length, fiber loading and chemical treatment of fiber on the physical and chemical properties of the sisal fiber reinforced polypropylene (SFRPP) composite material. The waste polypropylene and the treated and untreated sisal fiber with variable length and weight ratio (fiber/matrix ratio) were mixed. Flammability of sisal fiber reinforced Polypropylene (SFRPP) composites material was examined by a horizontal burning test according to ASTM D635 and chemical resistance of the sisal fibre reinforced PP composites was studied using ASTM D543 testing method. The result on the flammability test shows that treated fiber has lower burning rate than untreated fiber and decreases with increase in fiber length and fiber loading. The resistance of the composites to water has increased as the fiber length increases and decreased as the fiber loading increase. Generally, SFRPP composite is found to have better resistance to water than NaOH and H2SO4 and treating the fiber has brought considerable improvement on chemical resistance of the composite. Fiber loading and fiber length has positive and negative effect on the flammability of the SFRPP composite respectively.